Historia filozofii czy historia idei? Problem statusu metodologicznego historycznych badań nad rozwojem filozoficzno-religijnej myśli polskiej (Przegląd Religioznawczy – The Religious Studies Review, 2019)
The paper attempts a theoretical confrontation of two paradigms underlying contemporary historical reflection on the development of Polish philosophical and religious thought: the traditional paradigm of history of philosophy, and the paradigm of history of ideas which predominates in more recent research (and, to a certain extent, constitutes an alternative to the former). What is the general methodological status of scientific procedures employed within each of these approaches? Are these approaches qualitatively akin, i.e. aiming towards relatively equivalent cognitive goals using different theoretical means, or essentially competitive? Is there a mutual genealogical relationship underpinning the evolution of these paradigms? And finally, what factors determine the process of evolution from a metaphysical perspective? The aspects enumerated above, as well as other considerations related to the general problem outlined in the title of the paper, will constitute an attempt to assess the current state of research in this field.